Seletividade e dinâmica do S-Metolachlor em solos do estado do Paraná - Borges, Maiara Pinheiro da Silva (2024)
Beans are a staple food in Brazil, and weed control is essential for their productivity. The herbicide S-metolachlor, widely used in the country, has its dynamics underexplored in Brazilian soils. This study investigated the tolerance of bean genotypes and the interaction of the herbicide with different soils, aiming to optimize its use and promote sustainable agricultural practices. Five experiments were conducted in a greenhouse with two Brazilian soils: Latossolo Vermelho distroférrico (LVdf) and Argissolo Vermelho distrófico (PVd). The first study evaluated the tolerance of 19 bean genotypes (Phaseolus vulgaris and Vigna spp.) to S-metolachlor (1200 g a.i. ha-1 ). The genotypes showed varied responses, with Vigna spp., especially red Adzuki, being more sensitive, particularly in sandy soil. Pérola and Talismã beans demonstrated tolerance in both soils, with chlorophyll largely unaffected in most cases. The second study assessed the herbicide's dose-response and its efficacy against weeds such as papuã (Urochloa plantaginea) and sourgrass (Digitaria insularis). S-metolachlor was effective in controlling D. insularis and selective for Pérola and Talismã cultivars. However, U. plantaginea displayed soil-dependent behavior: it was tolerant in LVdf and sensitive in PVd, highlighting the influence of herbicide availability. The third study investigated S-metolachlor degradation in both soils. LVdf, with higher clay and organic matter content, exhibited faster degradation and a less pronounced residual effect compared to PVd, where the herbicide was more persistent. These results emphasize the importance of soil physicochemical properties in herbicide persistence and bioavailability. The fourth study evaluated herbicide sorption and desorption, revealing that the addition of corn straw significantly increased S-metolachlor sorption. In LVdf, sorption increased by 64%, while in PVd, the increase was 27.72%. This higher sorption reduced desorption, prolonging the herbicide's presence in the soil and enhancing its efficacy in weed control. Finally, the fifth study analyzed S-metolachlor leaching. Without straw, the herbicide remained in the surface soil layer. The addition of straw increased vertical mobility, with greater retention in LVdf and higher leaching in PVd. In summary, the studies highlighted the importance of considering S-metolachlor behavior in different soils and the influence of practices such as straw application. Understanding these factors allows for optimizing weed control, reducing environmental impacts, and ensuring bean productivity. These findings are crucial for developing more effective and sustainable agricultural strategies, benefiting soil health and crop production.